2020
DOI: 10.1177/0300060520941715
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable testosterone is associated with symptoms of depression in adult men

Abstract: Objective This study aimed to determine the relationship between serum testosterone levels and depressive symptoms in an adult male population. Methods We conducted a cross-sectional study of 1166 male participants from Zunyi, Guizhou, China. Each participant completed a questionnaire, a brief clinical exam, and had a fasting blood sample taken. We measured serum testosterone, sex hormone-binding globulin, and luteinizing hormone levels. Multiple linear regression was used to evaluate the effect of demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…27 As a result, our future research will likely focus on the lower levels of neuroactive steroids in certain regions of the brain, that has been observed previously to induce depression-like behavior. The findings of the previous study 28 revealed that repeated administration of finasteride for 7 days reduced hippocampal neurogenesis in rats.…”
Section: Discussionmentioning
confidence: 85%
“…27 As a result, our future research will likely focus on the lower levels of neuroactive steroids in certain regions of the brain, that has been observed previously to induce depression-like behavior. The findings of the previous study 28 revealed that repeated administration of finasteride for 7 days reduced hippocampal neurogenesis in rats.…”
Section: Discussionmentioning
confidence: 85%
“…Anti-inflammatory cytokines IL-10 and IL-4 and pro-inflammatory cytokines IL-1 β , IL-6, and TNF- α play a vital role in the occurrence and development of inflammation diseases [ 36 , 37 ]. A survey showed that the level of T in patients with depression was lower than that in normal people [ 38 ]. Furthermore, both preclinical evidence and clinical evidence showed that the low level of NPY directly led to a variety of mental illnesses, including depression and related diseases [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, because serum testosterone was not a static but a dynamic variable, measuring testosterone only once may cause some bias in testosterone levels used in the analysis. Third, in men's circulating plasma testosterone, approximately 2% to 3% is in free form, 33% to 54% is bound to albumin, and 44% to 65% is bound to sex hormone binding globulin, which loses its biological activity because of tight binding [ 32 ]. Bioavailable testosterone levels are not completely associated with testosterone levels.…”
Section: Discussionmentioning
confidence: 99%